Discovery of Heterobicyclic Templates for Novel Metabotropic Glutamate Receptor Subtype 5 Antagonists - Kulkarni, Santosh S. (2007)
Investigation of a series of heterobicyclic compounds with essential pharmacophoric features of the metabotropic glutamate receptor 5 (mGluR5) antagonists MPEP and MTEP provided novel structural templates with sub-micromolar affinities at the mGluR5.